Use of cerebrospinal fluid biomarkers in diagnosis of dementia across Europe - Hort, J; Bartos, A; Pirttilä, T; Scheltens, P (European journal of neurology, 2010)
BACKGROUND AND PURPOSE: Cerebrospinal fluid (CSF) biomarkers have been reported to be useful in dementia diagnosis. Not much is known about their use in clinical practice in Europe. METHODS: We analyzed data from a survey on the use of CSF biomarkers in the diagnosis of dementia across Europe using a questionnaire which was filled out by representatives of the 25 member countries of the European Federation of Neurological Societies (EFNS). RESULTS: Cerebrospinal fluid beta-amyloid, total tau, and phosphorylated tau proteins are frequently evaluated in the majority of the countries (in 18 out of 23 countries). No major technical or ethical issues were found that would hamper the procedure's ability to become routine in early and differential diagnostics of Alzheimer's disease. Cut-off values for beta-amyloid (median 500, range 300-849 pg/ml), total tau (367; 195-450 pg/ml) and phosphorylated tau (60; 40-85 pg/ml) varied considerably amongst countries and even within every country. CONCLUSIONS: Cerebrospinal fluid analysis of beta-amyloid, tau, and phosphorylated tau is frequently used in Europe. However, the use of various cut off values seriously hampers comparability and yields a potential threat to an interpretation and balanced use in clinical practice. We recommend that each laboratory establishes normative data and that multi-centered studies should be organized to explore the reasons for any differences.
Keywords: Phosphorylation; mozek; senzitivita a specificita; Sensitivity and Specificity; Humans; demence; lidé středního věku; fosforylace; Predictive Value of Tests; Female; Aged; mladý dospělý; dospělí; tau Proteins; senioři; lidé; Biomarkers; Europe; amyloidní beta-protein; proteiny tau; Adult; biologické markery; ženské pohlaví; Amyloid beta-Peptides; Male; Middle Aged; prediktivní hodnota testů; Brain; prognóza; Dementia; Young Adult; Prognosis; mužské pohlaví; Evropa